Analysis of Tax Impact on Corporate Debt Ratio: A Literature Study - Nurwanah, Andi; Sari, Ratna; Ikhtiari, Kirana; Muslim, Muslim (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This study examines the impact of tax policies on corporate debt ratios, focusing on domestic and multinational corporations across various industries. It aims to explore how tax shields and reforms influence firms' capital structure decisions. Research Design and Methodology: The research adopts a systematic literature review approach, synthesizing existing studies on tax policy, corporate debt, and financing strategies. The study comprehensively analyzes tax-driven corporate behavior in different tax environments by integrating findings from empirical studies and theoretical frameworks. Findings and Discussion: The findings reveal that tax shields significantly influence corporate debt strategies, especially in high-tax and capital-intensive industries. However, multinational corporations face additional challenges due to varying international tax regulations, leading to more conservative debt policies. The study also highlights how major tax reforms, such as the U.S. Tax Cuts and Jobs Act (TCJA), have led companies to reconsider their reliance on debt due to diminished tax advantages. Implications: The research underscores the importance of balanced tax planning for corporate finance managers while advising policymakers to design tax policies that encourage investment and financial stability. It suggests that firms consider broader economic risks alongside tax incentives when making capital structure decisions.